Solid electrolyte, composite positive electrode material and lithium-rich manganese-based solid-state battery

By providing a solid electrolyte suitable for lithium-rich manganese-based positive electrode active material, the problem of low adaptability between solid electrolyte and lithium-rich manganese-based positive electrode active material in the prior art is solved, and higher electrochemical performance and energy density are achieved .

CN119480948AInactive Publication Date: 2025-02-18SHENZHEN UNIV

Patent Information

Application Number
CN202411416364.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The low compatibility of existing solid electrolytes with lithium-rich manganese-based positive electrode active materials leads to unstable surface structure of the material and rapid decline in performance.

Method used

Provided is a solid electrolyte with the chemical formula of LiaMbNc, where M is one or more of P, S, In, Zr, Nb, Yb, Y, Hf, and N is the one of F, Cl, Br, I, O One or more, 0

Benefits of technology

It improves the suitability of solid electrolytes and lithium-rich manganese-based positive electrode active materials, enhances the electrochemical performance and energy density of the battery, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480948A_ABST
    Figure CN119480948A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, and discloses a solid-state electrolyte, a composite positive electrode material and a lithium-rich manganese-based solid-state battery. Wherein the chemical formula of the solid electrolyte is LiaMbNc, M is one or more of P, S, In, Zr, Nb, Yb, Y and Hf, and N is one or more of F, Cl, Br, I and O, 0 lt; a < = 7, 0 < b < = 6, and 0 < c < = 6. The solid electrolyte has a high voltage stability window, is resistant to high voltage and has extremely high ionic conductivity, the solid electrolyte is matched with a lithium-rich manganese-based positive electrode active material with low ionic conductivity, high stability is achieved, and the lithium-rich manganese-based solid-state battery prepared from the solid electrolyte has excellent electrochemical performance and can be applied to the field of lithium ion batteries. And the performance of the lithium-rich manganese-based positive electrode active material can be fully exerted due to relatively high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte, a composite positive electrode material, and a lithium-rich manganese-based solid-state battery. Background Art

[0002] As the core of lithium-ion batteries, the improvement of electrode material’s specific capacity is the key to enhancing battery’s specific energy. Positive electrode materials account for the highest mass proportion in batteries, so improving their specific capacity is particularly critical to improving battery performance. Positive electrode materials usually include positive electrode active materials, electrolytes and conductive agents. Currently, the specific capacity of commonly used positive electrode active materials such as LFP, LCO, LMO, Li-NCA and Li-NCM usually does not exceed 200mAh / g, while the specific capacity of lithium-rich manganese-based positive electrode active materials can be as high as 400mAh / g. In addition, they are abundant in resources and low in cost, showing broad application prospects.

[0003] However, the working voltage of lithium-rich manganese-based positive electrode active materials is high (2.0-4.8V), and their surface activity is enhanced, the side reactions with the electrolyte are more intense, and transition metal ions and oxygen ions are easily dissolved and precipitated, resulting in unstable surface structure of the material, thereby accelerating the decline of material performance. The existing solid electrolytes have low compatibility with lithium-rich manganese-based positive electrode active materials, and the performance of lithium-rich manganese-based positive electrode active materials cannot be brought into play when prepared into composite positive electrode materials. Therefore, a solid electrolyte with high compatibility with lithium-rich manganese-based positive electrode active materials is needed. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a solid electrolyte, a composite positive electrode material and a lithium-rich manganese-based solid-state battery, aiming to solve the problem of low compatibility between the existing solid electrolyte and the lithium-rich manganese-based positive electrode active material.

[0005] The technical solution of this application is as follows:

[0006] In a first aspect of the present application, a solid electrolyte is provided, wherein the chemical formula of the solid electrolyte is

[0007] Li a M b N c , wherein M is one or more of P, S, In, Zr, Nb, Yb, Y, Hf, N is one or more of F, Cl, Br, I, O, 0 <a≤7,0<b≤6,0<c≤6。

[0008] Preferably, the solid electrolyte includes one or more of Li3InCl6, Li2ZrCl6, LiNbOCl4, LiTaOCl4, and Li6PS5Cl.

[0009] In a second aspect of the present application, a composite cathode material is provided, which is made from raw materials including a lithium-rich manganese-based active material, a conductive agent, and the solid electrolyte of the first aspect of the present application.

[0010] Preferably, the chemical formula of the lithium-rich manganese-based active material is xLi2MnO3˙(1-x)LiMO2, where 0 < x < 1, and M is one or more of Mn, Ni, and Co; the conductive agent is one or more of Super-P, acetylene black, KS-6, CNT, graphene, and VGCF.

[0011] Preferably, the mass ratio of the lithium-rich manganese-based active material, the solid electrolyte, and the conductive agent is (50-70):(25-45):(0-25).

[0012] In a third aspect of the present application, a preparation method of the composite cathode material of the second aspect of the present application is provided, including the steps of: mixing the lithium-rich manganese-based active material, the solid electrolyte, and the conductive agent in proportion and then performing ball milling treatment to obtain the composite cathode material.

[0013] Preferably, the rotation speed of the ball milling treatment is 200-450 r / min, the time is 16-22 h, and the particle size of the composite cathode material is 7-10 μm.

[0014] In a fourth aspect of the present application, a lithium-rich manganese-based solid-state battery is provided, including the composite cathode material of the second aspect of the present application.

[0015] In a fifth aspect of the present application, a preparation method of the lithium-rich manganese-based solid-state battery of the fourth aspect of the present application is provided, including the steps of: providing a composite cathode material, a solid electrolyte sheet, and a negative electrode sheet; using the composite cathode material to coat one side of the solid electrolyte sheet, and then laminating the negative electrode sheet with the other side of the solid electrolyte sheet to obtain the lithium-rich manganese-based solid-state battery.

[0016] Preferably, the solid electrolyte sheet is obtained by pressing solid electrolyte powder, and the chemical formula of the solid electrolyte powder is Li a M b N c , where M is one or more of P, S, In, Zr, Nb, Yb, Y, and Hf, N is one or more of F, Cl, Br, I, and O, 0 < a ≤ 7, 0 < b ≤ 6, and 0 < c ≤ 6.

[0017] Advantages of the present application:

[0018] (1) The solid electrolyte of the present application has a high voltage stability window, high voltage resistance, and extremely high ionic conductivity. When it is matched with a lithium-rich manganese-based positive electrode active material with low ionic conductivity, it has high stability. The lithium-rich manganese-based solid-state battery prepared using the solid electrolyte of the present application has excellent electrochemical performance and high energy density, and fully exerts the performance of the lithium-rich manganese-based positive electrode active material;

[0019] (2) The lithium-rich manganese-based solid-state battery in the present application is prepared by a ball milling mold battery assembly method, which is easy to industrialize, environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for describing the embodiments are briefly introduced below.

[0021] Figure 1 This is a scanning electron microscope image of a cross section of the lithium-rich manganese-based solid-state battery in Example 1;

[0022] Figure 2 This is an in-situ AC impedance diagram of the lithium-rich manganese-based solid-state battery in Example 1;

[0023] Figure 3 CV curve diagram of the lithium-rich manganese-based solid-state battery in Example 1;

[0024] Figure 4 is a cycle diagram of the lithium-rich manganese-based solid-state battery in Example 1;

[0025] Figure 5 The charge and discharge curves of the lithium-rich manganese-based solid-state battery in Examples 1-4;

[0026] Figure 6 It is a charge and discharge curve diagram of the lithium-rich manganese-based solid-state battery in Comparative Example 1;

[0027] Figure 7 This is the charge and discharge curve of the lithium-rich manganese-based solid-state battery in Comparative Example 2. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings and embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0029] It should be noted that terms such as "upper", "lower", "left", "right", "middle" cited in this specification are only for the convenience of clear narration and are not used to limit the scope of implementation. The change or adjustment of their relative relationship, without substantial change in the technical content, should also be regarded as the scope of implementation of this application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this application belongs.

[0030] Solid electrolytes can be classified into types such as oxides, sulfides, polymers, and composite electrolytes according to their structures and compositions. Oxide solid electrolytes have a relatively wide voltage window and high chemical stability, but at room temperature, they have low ionic conductivity, high hardness, and are not easy to process, resulting in complex preparation processes and large interfacial impedance. Sulfide electrolytes exhibit higher ionic conductivity and good mechanical properties, but the interfacial reaction with active substances, the narrow electrochemical window, and high sensitivity to air make the requirements for their preparation and application environment relatively high. Polymer electrolytes have good flexibility and production convenience, but poor thermal stability and a relatively low oxidation voltage window. It can be seen that existing solid electrolytes cannot both adapt to the high working voltage of lithium-rich manganese-based cathode active materials while being relatively stable and having good conductivity.

[0031] Based on this, an embodiment of this application provides a solid electrolyte, and the chemical formula of the solid electrolyte is Li a M b N c , where M is one or more of P, S, In, Zr, Nb, Yb, Y, Hf, and N is one or more of F, Cl, Br, I, O, 0 < a ≤ 7, 0 < b ≤ 6, 0 < c ≤ 6.

[0032] In some embodiments, the solid electrolyte includes one or more of Li3InCl6, Li2ZrCl6, LiNbOCl4, LiTaOCl4, Li6PS5Cl.

[0033] An embodiment of this application also provides a composite cathode material, which is made from raw materials including a lithium-rich manganese-based active material, a conductive agent, and the solid electrolyte as described above in this embodiment of the application.

[0034] Furthermore, the chemical formula of the lithium-rich manganese-based active material is xLi2MnO3˙(1 - x)LiMO2, where 0 < x < 1, and M is one or more of Mn, Ni, Co; the conductive agent is one or more of Surpe-P, acetylene black, KS-6, CNT, graphene, VGCF.

[0035] In some embodiments, the mass ratio of the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent is (50-70): (25-45): (0-25). For example, the mass ratio of the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent is 50:25:25, 50:45:5, 55:40:5, 60:35:5, 65:30:5 or 70:25:5, etc. Preferably, the mass ratio of the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent is 50:45:5, 55:40:5, 60:35:5, 65:30:5. More preferably, the mass ratio of the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent is 50:45:5. The composite positive electrode material is prepared when the mass ratio of the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent is 50:45:5, and the lithium-rich manganese-based solid-state battery prepared from the prepared composite positive electrode material has better electrochemical performance.

[0036] The present application also provides a method for preparing the composite positive electrode material as described above in the present application, comprising the steps of: mixing a lithium-rich manganese-based active material, a solid electrolyte and a conductive agent in proportion and then subjecting the mixture to ball milling to obtain a composite positive electrode material. The ratio of the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent is (50-70): (25-45): (0-25), and the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent are the same as those described above, and are not described in detail herein.

[0037] In some embodiments, the step of ball milling treatment may be to mix the lithium-rich manganese-based active material, the solid electrolyte and the conductive agent in proportion and then use a planetary ball mill for ball milling treatment, the speed of the ball milling treatment is 200-450r / min, for example, the speed of the ball milling treatment may be 200r / min, 250r / min, 300r / min, 350r / min, 400r / min or 450r / min, etc. The time of ball milling treatment is 16-22h, for example, the time of ball milling treatment may be 16h, 17h, 18h, 19h, 20h, 21h or 22h, etc. The particle size of the composite positive electrode material after ball milling treatment is 7-10μm, for example, the particle size of the composite positive electrode material after ball milling treatment is 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm, etc.

[0038] The present application also provides a lithium-rich manganese-based solid-state battery, including the composite positive electrode material described above in the present application. Further, the lithium-rich manganese-based solid-state battery also includes a solid electrolyte and a negative electrode material, and the composite positive electrode material, the solid electrolyte and the negative electrode material can be in sheet form. In some embodiments, the negative electrode sheet (sheet negative electrode material) is a lithium-indium alloy sheet.

[0039] The present application also provides a method for preparing the lithium-rich manganese-based solid-state battery as described above in the present application, comprising the steps of:

[0040] A composite positive electrode material, a solid electrolyte sheet and a negative electrode sheet are provided; one side of the solid electrolyte sheet is coated with the composite positive electrode material, and then the negative electrode sheet is bonded to the other side of the solid electrolyte sheet to obtain a lithium-rich manganese-based solid-state battery.

[0041] Among them, the specific composition of the composite positive electrode material, the solid electrolyte sheet and the negative electrode sheet is the same as above and will not be repeated. The solid electrolyte sheet can be obtained by pressing a powdered solid electrolyte. For example, the solid electrolyte (powder) can be added to a tableting mold and maintained at a pressure of 400-600MPa for 1-2min to obtain a solid electrolyte sheet. For example, the pressing pressure can be 400MPa, 450MPa, 500MPa, 550MPa or 600MPa, etc., and the holding time can be 1min, 70s, 80s, 90s, 100s, 110s or 2min, etc.

[0042] In some embodiments, the step of coating one side of the solid electrolyte sheet with a composite positive electrode material may be: evenly sprinkle the composite positive electrode material powder on the surface of one side of the electrolyte sheet, place the electrolyte sheet sprinkled with the composite positive electrode material powder in a tableting mold, and hold the pressure at a pressure of 400-600 MPa for 2-4 minutes. For example, the pressing pressure may be 400 MPa, 450 MPa, 500 MPa, 550 MPa or 600 MPa, and the holding time may be 2 minutes, 2 minutes and 30 seconds, 3 minutes, 3 minutes and 30 seconds, or 4 minutes.

[0043] In some embodiments, the step of bonding the negative electrode sheet to the other side of the solid electrolyte sheet may be: placing the negative electrode sheet on the side of the solid electrolyte sheet coated with the composite positive electrode material away from the composite positive electrode material, and pressing the two together through a tablet pressing mold.

[0044] The following is further described by means of specific examples.

[0045] Example 1

[0046] (1) Li-rich manganese-based cathode material Li 1.2 Mn 0.6 Ni 0.2 O2, solid electrolyte LiNbOCl4 and conductive agent VGCV are mixed in a ratio of 50:45:5, and then ball-milled using a planetary ball mill at a ball milling speed of 250 r / min for 20 h to obtain a composite positive electrode material powder with a particle size range of about 7-10 μm;

[0047] (2) adding solid electrolyte LiNbOCl4 (powder) into a tablet pressing mold and maintaining the pressure at 500 MPa for 1-2 minutes to obtain a solid electrolyte sheet;

[0048] (3) Sprinkle the composite positive electrode material Li evenly on one side of the solid electrolyte sheet. 1.2 Mn 0.6 Ni 0.2 O2, maintained at 500 MPa for 3 min;

[0049] (4) A lithium-indium alloy sheet is added to the other side of the solid electrolyte sheet, and the two are bonded together using a sheet pressing mold to produce a lithium-rich manganese-based solid-state battery.

[0050] Example 2

[0051] (1) Li-rich manganese-based cathode material Li 1.2 Mn 0.6 Ni 0.2 O2, solid electrolyte LiNbOCl4 and conductive agent VGCV are mixed in a ratio of 55:40:5, and then ball-milled using a planetary ball mill at a ball milling speed of 250 r / min for 20 h to obtain a composite positive electrode material powder with a particle size range of about 7-10 μm;

[0052] (2) adding solid electrolyte LiNbOCl4 (powder) into a tablet pressing mold and maintaining the pressure at 500 MPa for 1-2 minutes to obtain a solid electrolyte sheet;

[0053] (3) Sprinkle the composite positive electrode material Li evenly on one side of the solid electrolyte sheet. 1.2 Mn 0.6 Ni 0.2 O2, maintained at 500 MPa for 3 min;

[0054] (4) A lithium-indium alloy sheet is added to the other side of the solid electrolyte sheet, and the two are bonded together using a sheet pressing mold to produce a lithium-rich manganese-based solid-state battery.

[0055] Example 3

[0056] (1) Li-rich manganese-based cathode material Li 1.2 Mn 0.6 Ni 0.2 O2, solid electrolyte LiNbOCl4 and conductive agent VGCV are mixed in a ratio of 60:35:5, and then ball-milled using a planetary ball mill at a ball milling speed of 250 r / min for 20 h to obtain a composite positive electrode material powder with a particle size range of about 7-10 μm;

[0057] (2) adding solid electrolyte LiNbOCl4 (powder) into a tablet pressing mold and maintaining the pressure at 500 MPa for 1-2 minutes to obtain a solid electrolyte sheet;

[0058] (3) Sprinkle the composite positive electrode material Li evenly on one side of the solid electrolyte sheet. 1.2 Mn 0.6 Ni 0.2 O2, maintained at 500 MPa for 3 min;

[0059] (4) A lithium-indium alloy sheet is added to the other side of the solid electrolyte sheet, and the two are bonded together using a sheet pressing mold to produce a lithium-rich manganese-based solid-state battery.

[0060] Example 4

[0061] (1) Li-rich manganese-based cathode material Li 1.2 Mn 0.6 Ni 0.2 O2, solid electrolyte LiNbOCl4 and conductive agent VGCV are mixed in a ratio of 65:30:5, and then ball-milled using a planetary ball mill at a ball milling speed of 250 r / min for 20 h to obtain a composite positive electrode material powder with a particle size range of about 7-10 μm;

[0062] (2) adding solid electrolyte LiNbOCl4 (powder) into a tablet pressing mold and maintaining the pressure at 500 MPa for 1-2 minutes to obtain a solid electrolyte sheet;

[0063] (3) Sprinkle the composite positive electrode material Li evenly on one side of the solid electrolyte sheet. 1.2 Mn 0.6 Ni 0.2 O2, maintained at 500 MPa for 3 min;

[0064] (4) A lithium-indium alloy sheet is added to the other side of the solid electrolyte sheet, and the two are bonded together using a sheet pressing mold to produce a lithium-rich manganese-based solid-state battery.

[0065] Comparative Example 1

[0066] The lithium-rich manganese-based cathode material Li 1.2 Mn 0.6 Ni 0.2 O2, solid electrolyte Li6PS5Cl and conductive agent VGCV are mixed in a ratio of 50:45:5, and then ball-milled using a planetary ball mill at a ball milling speed of 250 r / min for 20 h to obtain a composite cathode material powder with a particle size range of about 7-10 μm;

[0067] (2) adding solid electrolyte Li6PS5Cl (powder) into a tablet pressing mold and maintaining the pressure at 500 MPa for 1-2 min to obtain a solid electrolyte sheet;

[0068] (3) Sprinkle the composite positive electrode material Li evenly on one side of the solid electrolyte sheet. 1.2 Mn 0.6 Ni 0.2 O2, maintained at 500 MPa for 3 min;

[0069] (4) A lithium-indium alloy sheet is added to the other side of the solid electrolyte sheet, and the two are bonded together using a sheet pressing mold to produce a lithium-rich manganese-based solid-state battery.

[0070] Comparative Example 2

[0071] The lithium-rich manganese-based cathode material Li 1.2 Mn 0.6 Ni 0.2 O2, solid electrolyte Li3InCl6 and conductive agent VGCV are mixed in a ratio of 50:45:5, and then ball-milled using a planetary ball mill at a ball milling speed of 250 r / min for 20 h to obtain a composite positive electrode material powder with a particle size range of about 7-10 μm;

[0072] (2) adding solid electrolyte Li3InCl6 (powder) into a tablet pressing mold and maintaining the pressure at 500 MPa for 1-2 minutes to obtain a solid electrolyte sheet;

[0073] (3) Sprinkle the composite positive electrode material Li evenly on one side of the solid electrolyte sheet. 1.2 Mn 0.6 Ni 0.2 O2, maintained at 500 MPa for 3 min;

[0074] (4) A lithium-indium alloy sheet is added to the other side of the solid electrolyte sheet, and the two are bonded together using a sheet pressing mold to produce a lithium-rich manganese-based solid-state battery.

[0075] Test Example 1

[0076] The test methods used in this test example are all conventional test methods in the art, and the specific test steps are not repeated here. The cross section of the lithium-rich manganese-based solid-state battery prepared in Example 1 was observed using a scanning electron microscope. The results are as follows: Figure 1 shown. Figure 1 The upper middle layer is the lithium indium negative electrode sheet, the middle layer is the solid electrolyte sheet, and the lower layer is the composite positive electrode material. Figure 1 It can be seen that the three have a high degree of fit and a smooth contact surface.

[0077] The lithium-rich manganese-based solid-state battery prepared in Example 1 was subjected to an in-situ AC impedance test. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that during the entire charge and discharge process, the interfacial impedance of the battery remains basically unchanged, indicating that the interface deterioration of the battery before and after charge and discharge is small.

[0078] The CV curve of the lithium-rich manganese-based solid-state battery prepared in Example 1 was tested by cyclic voltammetry. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that at a scan rate of 0.1 mV / s, the voltage offset of the all-solid-state battery of Example 1 is only about 0.1 V, indicating that the lithium-rich manganese-based solid-state battery prepared in Example 1 has excellent electrochemical properties, and further indicates that the solid electrolyte in the embodiment of the present application has a high degree of compatibility with the lithium-rich manganese-based positive electrode active material.

[0079] The lithium-rich manganese-based solid-state battery prepared in Example 1 was subjected to a cycle test, and the results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the lithium-rich manganese-based solid-state battery prepared in Example 1 has a higher capacity and cycle retention rate.

[0080] Test Example 2

[0081] The test methods used in this test example are all conventional test methods in the field, and the specific test steps are not repeated here. The charge and discharge curves of the lithium-rich manganese-based solid-state batteries of Examples 1-4 were tested respectively, and the results are as follows: Figure 5 As shown. Figure 5 It can be seen that the electrochemical performance of the lithium-rich manganese-based solid-state battery prepared in Example 1 is the best.

[0082] Test Example 3

[0083] The lithium-rich manganese-based solid-state battery prepared in Comparative Example 1 was subjected to charge and discharge tests. The results are as follows: Figure 6 As shown, combined Figure 5 and Figure 6 It can be seen that compared with the lithium-rich manganese-based solid-state battery prepared in Example 1, the first efficiency and discharge specific capacity of the lithium-rich manganese-based solid-state battery prepared in Comparative Example 1 are lower than those of the lithium-rich manganese-based solid-state battery prepared in Example 1.

[0084] Test Example 4

[0085] The lithium-rich manganese-based solid-state battery prepared in Comparative Example 2 was subjected to charge and discharge tests. The results are as follows: Figure 7 As shown, combined Figure 5 and Figure 7 It can be seen that compared with the lithium-rich manganese-based solid-state battery prepared in Example 1, the first efficiency and discharge specific capacity of the lithium-rich manganese-based solid-state battery prepared in Comparative Example 2 are lower than those of the lithium-rich manganese-based solid-state battery prepared in Example 1.

[0086] In summary, the solid electrolyte of the present application has a high degree of compatibility with the lithium-rich manganese-based positive electrode active material. The lithium-rich manganese-based solid-state battery prepared using the solid electrolyte in the present application has excellent electrochemical properties and a high energy density, and fully exerts the performance of the lithium-rich manganese-based positive electrode active material. The lithium-rich manganese-based solid-state battery in the present application is prepared by an assembly method of a ball milling mold battery, which is easy to industrialize, environmentally friendly, and low-cost.

[0087] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.

Claims

1. A solid electrolyte, characterized in that The chemical formula of the solid electrolyte is Li a M b N c , wherein M is one or more of P, S, In, Zr, Nb, Yb, Y, Hf, N is one or more of F, Cl, Br, I, O, 0 <a≤7,0<b≤6,0<c≤6。 2. The solid electrolyte according to claim 1, characterized in that The solid electrolyte includes one or more of Li3InCl6, Li2ZrCl6, LiNbOCl4, LiTaOCl4, and Li6PS5Cl.

3. A composite positive electrode material, characterized in that: The composite cathode material includes a lithium-rich manganese-based active material, a conductive agent, and the solid electrolyte described in claim 1 or 2.

4. The composite positive electrode material according to claim 3, characterized in that: The chemical formula of the lithium-rich manganese-based active material is xLi2MnO3˙(1-x)LiMO2, where 0 < x < 1, and M is one or more of Mn, Ni, and Co; The conductive agent is one or more of Surpe-P, acetylene black, KS-6, CNT, graphene, and VGCF.

5. The composite positive electrode material according to claim 3, characterized in that: The mass ratio of the lithium-rich manganese-based active material, the solid electrolyte, and the conductive agent is (50-70):(25-45):(0-25).

6. A method for preparing the composite positive electrode material according to any one of claims 3 to 5, characterized in that: It includes the steps of: mixing the lithium-rich manganese-based active material, the solid electrolyte, and the conductive agent in proportion and then performing ball milling treatment to obtain a composite cathode material.

7. The method for preparing a composite positive electrode material according to claim 6, characterized in that: The rotation speed of the ball milling treatment is 200-450 r / min, the time is 16-22 h, and the particle size of the composite cathode material is 7-10 μm.

8. A lithium-rich manganese-based solid-state battery, characterized in that: It includes the composite cathode material according to any one of claims 3 to 5.

9. A method for preparing a lithium-rich manganese-based solid-state battery according to claim 8, characterized in that: It includes the steps of: providing a composite cathode material, a solid electrolyte sheet, and a negative electrode sheet; using the composite cathode material to coat one side of the solid electrolyte sheet, and then laminating the negative electrode sheet to the other side of the solid electrolyte sheet to obtain a lithium-rich manganese-based solid-state battery.

10. The method for preparing a lithium-rich manganese-based solid-state battery according to claim 9, characterized in that: The solid electrolyte sheet is obtained by pressing solid electrolyte powder, and the chemical formula of the solid electrolyte powder is Li a M b N c , wherein M is one or more of P, S, In, Zr, Nb, Yb, Y, Hf, N is one or more of F, Cl, Br, I, O, 0 <a≤7,0<b≤6,0<c≤6。

Citation Information

Patent Citations

  • Lithium-rich manganese-based all-solid-state lithium battery with high interface compatibility and preparation method thereof

    CN114843616A

  • Electrolyte-coated positive electrode material as well as preparation method and application thereof

    CN116741935A

  • All-solid-state secondary battery and preparation method thereof

    CN117039133A

  • Surface-modified lithium-rich manganese-based positive electrode material with multi-layer core-shell structure and preparation method of surface-modified lithium-rich manganese-based positive electrode material

    CN118016841A

  • Solid electrolyte material and battery using the same

    US20210296692A1

Cited By

  • Semi-solid-state battery positive electrode slurry, semi-solid-state positive plate and semi-solid-state battery

    CN120527390A